Genotype-phenotype associations in dilated cardiomyopathy: meta-analysis on more than 8000 individuals - Kayvanpour, Elham; Sedaghat-Hamedani, Farbod; Amr, Ali; Lai, Chung Lun Alan; Haas, Jan; Holzer, Daniel Benjamin; Frese, Karen S.; Jensen, Katrin; Katus, Hugo; Meder, Benjamin (Clinical research in cardiology, 2017)
AimsRoutine genetic testing in Dilated Cardiomyopathy (DCM) has recently become reality using Next-Generation Sequencing. Several studies have explored the relationship between genotypes and clinical phenotypes to support risk estimation and therapeutic decisions, however, most studies are small or restricted to a few genes. This study provides to our knowledgke the first systematic meta-analysis on genotype-phenotype associations in DCM.Methods and resultsWe retrieved PubMed/Medline literature on genotype-phenotype associations in patients with DCM and mutations in LMNA, PLN, RBM20, MYBPC3, MYH7, TNNT2 and TNNI3. We summarized and extensively reviewed all studies that passed selection criteria and performed a meta-analysis on key phenotypic parameters. Together, 48 studies with 8097 patients were included. Furthermore, we reviewed recent studies investigating genotype-phenotype associations in DCM patients with TTN mutations. The average frequency of mutations in the investigated genes was between 1 and 5 %. The mean age of DCM onset was the beginning of the fifth decade for all genes. Heart transplantation (HTx) rate was highest in LMNA mutation carriers (27 %), while RBM20 mutation carriers were transplanted at a markedly younger age (mean 28.5 years). While 73 % of DCM patients with LMNA mutations showed cardiac conduction diseases, low voltage was the reported ECG hallmark in PLN mutation carriers. The frequency of ventricular arrhythmia in DCM patients with LMNA (50 %) and PLN (43 %) mutations was significantly higher. The penetrance of DCM phenotype in subjects with TTN truncating variants increased with age and reached 100 % by age of 70.ConclusionA pooled analysis of available genotype-phenotype data shows a higher prevalence of sudden cardiac death (SCD), cardiac transplantation, or ventricular arrhythmias in LMNA and PLN mutation carriers compared to sarcomeric gene mutations. This study will further support the clinical interpretation of genetic findings.